"Documents, Please": Advances in Social Protection and Birth Certification in the Developing World. (23rd February 2016) - Hunter, Wendy; Brill, Robert
Abstract : A birth certificate is essential to exercising citizenship, yet vast numbers of poor people in developing countries have no official record of their existence. Few academic studies analyze the conditions under which governments come to document and certify births routinely, and those that do leave much to be explained, including why nontotalitarian governments at low to middle levels of economic development come to prioritize birth registration. This article draws attention to the impetus that welfare-building initiatives give to identity documentation. The empirical focus is on contemporary Latin America, where extensions in institutionalized social protection since the 1990s have increased the demand for and supply of birth registration, raising the life chances of the poor and building state infrastructure in the process. The authors' argument promises to have broader applicability as welfare states form in other developing regions.